2020
DOI: 10.1101/2020.06.17.20134015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Genetic Host Response Risk Factors in Severe COVID-19 Patients

Abstract: BACKGROUND Epidemiological studies indicate that as many as 20% of individuals who test positive for COVID-19 develop severe symptoms that can require hospitalization. These symptoms include low platelet count, severe hypoxia, increased inflammatory cytokines and reduced glomerular filtration rate. Additionally, severe COVID-19 is associated with several chronic co-morbidities, including cardiovascular disease, hypertension and type 2 diabetes mellitus. The identification of genetic risk factors that impact d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 122 publications
(126 reference statements)
5
36
0
Order By: Relevance
“…In addition to possible involvement of several other genes (e.g., ABO blood type and Mediterranean fever gene) [ 99 ], genetic variations in these gateways might be influenced by the societies geographically. Using a combinational analysis approach, Taylor and colleagues identified 68 protein-coding genes that were highly associated with severe COVID-19 [ 100 ]. Ouyang et al revealed that the number of differentially expressed genes ( DEGs ) increased by disease progression and decreased after initial treatment.…”
Section: Why Some Children Experience More Severe Illness?mentioning
confidence: 99%
“…In addition to possible involvement of several other genes (e.g., ABO blood type and Mediterranean fever gene) [ 99 ], genetic variations in these gateways might be influenced by the societies geographically. Using a combinational analysis approach, Taylor and colleagues identified 68 protein-coding genes that were highly associated with severe COVID-19 [ 100 ]. Ouyang et al revealed that the number of differentially expressed genes ( DEGs ) increased by disease progression and decreased after initial treatment.…”
Section: Why Some Children Experience More Severe Illness?mentioning
confidence: 99%
“…Along these same lines, Taylor et al (2020) identified 68 genes involved with response to SARS‐CoV‐2 infection. These included loci that encode pro‐inflammatory cytokines, endothelial cell dysfunction, and viral susceptibility factors, among other cellular products.…”
Section: Genetic Risk Factorsmentioning
confidence: 96%
“…Some people infected with SARS‐CoV‐2 become extremely sick, while others express only mild symptoms or are asymptomatic. Among the severe symptoms are increased inflammatory cytokines, low platelet count, severe hypoxia, and reduced kidney function, (Taylor et al, 2020). Preexisting conditions or chronic co‐morbidities such as diabetes, hypertension, cardiovascular disease, cancer and chronic respiratory illnesses such as asthma and COPD also put people at higher risk for infection and severe disease symptoms (Caramelo, Ferreira, & Oliveiros, 2020; Guan et al, 2020; Jain & Yuan, 2020; Taylor et al, 2020; Wang et al, 2020; Yang et al, 2020).…”
Section: Sars‐cov‐2 Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations